El TLC Perú - China: Posibles implicancias para el Perú - Torres Cuzcano, Víctor (2010)
The paper analyzes the Free Trade Agreement (FTA ) between Peru and China signed in Pekin on April 28, 2009, and ratified by Peru on December 6 of the same year. It seeks to identify the possible risks that this one might imply for certain sensitive sectors of the national industry, and hence for the development of Peru. It has been organized in three parts. In the first one, there is a brief state of situation of the commercial exchange and the flow of direct investments between both countries. The second one, analyze the process of negotiation of the FTA and his principal results (trade of goods, services, and investments). The third part, presents the evolution of the chinese imports in those industries particularly sensitive to the FTA .